2019
DOI: 10.1002/jpln.201800652
|View full text |Cite
|
Sign up to set email alerts
|

Testing mechanisms underlying the Hedley sequential phosphorus extraction of soils

Abstract: The Hedley fractionation has become the preeminent measure for estimating the bioavailability of phosphorus (P) in soils. However, mechanisms underlying P extractability have never been tested. We hypothesize that P sequentially extracted by individual steps can either be referred to a specific mineral source (Hypothesis 1) or to its binding strength to minerals (Hypothesis 2). We prepared mineral‐P associations in the laboratory using various secondary mineral phases and P forms (orthophosphate, phytic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…In a mesocosm experiment, Andrino et al (2019) showed that arbuscular mycorrhiza in symbiosis with tomato were able to acquire orthophosphate and phytate from associations with goethite. Again, more P was plant-available in the treatment with inorganic P. This finding is consistent with the observation that more goethite-associated phosphate than phytate was extractable by an anion exchange resin in HCO 3 − form, which mimics a plant root taking up P (Klotzbücher et al, 2019). In a hydroponic experiment, palisade grass and ruzigrass took up orthophosphate that was associated with goethite or amorphous Al oxide (Merlin et al, 2016).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In a mesocosm experiment, Andrino et al (2019) showed that arbuscular mycorrhiza in symbiosis with tomato were able to acquire orthophosphate and phytate from associations with goethite. Again, more P was plant-available in the treatment with inorganic P. This finding is consistent with the observation that more goethite-associated phosphate than phytate was extractable by an anion exchange resin in HCO 3 − form, which mimics a plant root taking up P (Klotzbücher et al, 2019). In a hydroponic experiment, palisade grass and ruzigrass took up orthophosphate that was associated with goethite or amorphous Al oxide (Merlin et al, 2016).…”
Section: Introductionsupporting
confidence: 84%
“…The factors limiting P uptake depicted by Lambers et al (2008) might also explain why our results differ from results of Merlin et al (2016) and Klotzbücher et al (2019). In the study of Klotzbücher et al (2019) it was shown that 43% of goethiteassociated phosphate and 6% of goethite-associated phytate were extracted by an anion exchange resin in HCO 3 − form, which mimics a plant root taking up P. The resin was placed together with P-loaded goethite in ultrapure water. Phosphorus release was driven by the chemical gradient of P between goethite and solution, and an equilibrium state was permanently changed by P removal by the resin.…”
Section: Phosphorus From Lüss Subsoil and From The Added Adsorption Complexes Is Not Available To Beechmentioning
confidence: 63%
See 1 more Smart Citation
“…The remaining residue fraction extracted mainly recalcitrant P. Additionally, acid-digestible Al and Fe were determined on a subset of the soil using microwave digestion as above. We acknowledge that the Hedley fractionation forms are "operationally defined" and are limited in specifically defining different P forms (see, for instance, Klotzbücher et al, 2019) but still a useful approach in comparative studies like ours to investigate the fate of native P in managed systems as suggested in a review by Negassa and Leinweber (2009).…”
Section: Soil Sampling and Ion-exchange Resin Capsulesmentioning
confidence: 99%
“…This decrease is concurrent with increasing soil N:P ratios in the topsoil (0-30 cm) along the gradient, and decreasing P concentration in the litterfall, including leaf litter and fine roots in forest floor and mineral soil ( Table 1). Such a decreasing trend along the gradient is less remarkable in soil P content (mg P/kg soil) and available P content [mg P/kg soil, resin P and NaHCO 3 extracted P in Hedley fractionation (Klotzbücher et al, 2019)], due to a noticeably lower stone content at MTF than VES ( Table 1). Other soil properties, including soil organic and microbial C contents as well as soil and microbial C:N:P ratios, do not show clear trends along the total soil P gradient.…”
Section: Descriptions Of Study Sitesmentioning
confidence: 99%